Anticipations of the Crisis: On the Similarities between post-Keynesian Economics and Regulation Theory - Mark Setterfield (Revue de la Régulation)
This paper explores the similarities between post-Keynesian Economics (PKE) and Regulation Theory (RT). It is argued that, despite important differences between these traditions, the analytical contents of PKE and RT display broad similarities with respect to their treatments of the income-generating process, the crisis-prone nature of capitalism, and the institutional contingency of capitalist growth and development. This thesis is then exemplified and substantiated with reference to the 2007—2009 financial crisis and “Great Recession”. Specifically, it is shown that important strands of both PKE and RT characterize and were successful in anticipating the crisis as resulting from the exhaustion of a financialized growth process.